Answer:
It is equivalent to 15x – 3)(2x + 1) = 0. False
It is equivalent to (5x – 3)(2x + 1) = 0 True
Either x=-1/2 or 5/3
Step-by-step explanation:
Consider the equation 5x (2x + 1) - 3(2x + 1) = 0.
It is equivalent to 15x – 3)(2x + 1) = 0. False
It is equivalent to (5x – 3)(2x + 1) = 0 True
When you take pull-out (2x+1), you will be left with (5x-3)
5x (2x + 1) - 3(2x + 1) = 0.
(2x+1)(5x-3)=0
Either 2x + 1 = 0
2x = -1
Divide both-side of the equation by 2
2x/2 = -1/2
x= -1/2
OR
5x-3 =0
5x = 3
Divide both-side of the equation by 5
5x/5 = 3/5
x = 5/3
Either x=-1/2 or 5/3
The answer is: 54 inches would be too long for a shoelace
If I managed to help you, please make sure to mark my answer as the "Brainliest" answer. Thanks! :)
Day 1 - 100
Day 2 - 50
Day 3 - 25
Day 4 - 15
Day 5 - 10
Day 6 - 5
Day 7 - 2.5
Answer:
See answers and explanations
Step-by-step explanation:
A) Discriminant = b² - 4ac = (12)² - 4(9)(4) = 144 - 144 = 0
B) Since the discriminant is 0, this means the equation only has one root.
C) The root is real in this case since the discriminant is not negative. Otherwise, we would have two imaginary roots if it were (remember that complex roots come in pairs)
To find the area of this figure, there is two choices
1. cut it into 3 rectangles.
2.find the missing rectangle in the middle......
I likes 2 better $_$ :}
find the missing area in the middle, 12* 23 = 276
the area of the whole figure 31*69-276=1863m²